Team cognitive flexibility, team adaptation and performance: An experimental approach. - Passos, A. M.; Santos, C. M.; Silva, A.; Broda, A.; Uitdewilligen, S. (13th INGRoup Annual Conference, 2018)
This study aims to analyse the effect of cognitive flexibility on task mental model similarity, team adaptation, and performance. Thirty-eight teams performed a computer-based real-time command-and-control firefighting simulation. Findings suggest that the cognitive flexibility manipulation has an effect on task mental model similarity, but not on team adaptation and performance.